The impact of the initial stance position on lower limb joint kinetics in the taekwondo roundhouse kick - Daniel Jandačka; Isaac Estevan; Miroslav Janura; Coral Falco (Palacky University, 2013)
BACKGROUND: To achieve good performance, taekwondo athletes should optimize the stance position of the foot on the ground. OBJECTIVE: The aim of this study is to compare generated net joint power (hip, knee and ankle) during stance phase, magnitude of peak foot velocity of the attacking lower extremity and execution stance time produced from three stance positions (forward "0°", diagonal "45°", orthogonal "90°") in the taekwondo roundhouse kick. METHODS: Ten taekwondo athletes participated in the study; their experience of practicing taekwondo ranged between 13.8 ± 5.8 years. The kinetics and kinematics of the athletes' movement during the roundhouse kick were recorded. The execution stance time and the magnitude of peak foot velocity were determined. The net joint power of the kicking lower extremity during the stance phase was calculated using the inverse dynamics method. Then the peak net joint power was determined. RESULTS: The analysis of variance for repeated measures showed that there is a significant main effect of the stance position on the peak net hip joint power in the three planes. In addition, the stance position does not affect the magnitude of the peak foot velocity of the kicking lower extremity and execution stance time. CONCLUSIONS: The necessity to produce a higher net hip joint power in the stance phase of the roundhouse kick from the position when the feet are placed orthogonal to the target of the kick, compared with the execution of the kick from the forward or diagonal position, must be taken into account for purposes of rationalizing strength training of taekwondo athletes or for selecting the technique of the roundhouse kick.